2008
DOI: 10.1136/bmj.a2002
|View full text |Cite
|
Sign up to set email alerts
|

The joint impact on being overweight of self reported behaviours of eating quickly and eating until full : cross sectional survey

Abstract: Objective To examine whether eating until full or eating quickly or combinations of these eating behaviours are associated with being overweight. Design and participants Cross sectional survey. Setting Two communities in Japan. Results 571 (50.9%) men and 1265 (58.4%) women self reported eating until full, and 523 (45.6%) men and 785 (36.3%) women self reported eating quickly. For both sexes the highest age adjusted mean values for height, weight, body mass index, and total energy intake were in the eating unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
210
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(244 citation statements)
references
References 21 publications
(24 reference statements)
19
210
2
7
Order By: Relevance
“…The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters. This is consistent with the findings of many previous studies of the relationships between the objectively and subjectively assessed eating speeds and the body composition and shape (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have also demonstrated that fast eating induces overeating, and that overeating is related to weight gain due to the ingestion of a larger volume of food before experiencing satiety (22)(23)(24).…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters. This is consistent with the findings of many previous studies of the relationships between the objectively and subjectively assessed eating speeds and the body composition and shape (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have also demonstrated that fast eating induces overeating, and that overeating is related to weight gain due to the ingestion of a larger volume of food before experiencing satiety (22)(23)(24).…”
supporting
confidence: 92%
“…Cross-sectional, longitudinal and experimental studies have provided strong evidence for fast eating inducing overweight (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Healthy eating behaviors were evaluated by summing the score of eating behaviors each subject reported at baseline and follow-up in terms of the following: avoiding salty foods (Li et al 2010), eating breakfast almost daily (van der Heijden et al 2007), eating fast (Otsuka et al 2006), and not eating until full (Maruyama et al 2008). Smoking status was classified as never or current smoking.…”
Section: Health Questionnairementioning
confidence: 99%